FACTORS ASSOCIATED WITH HEALTH SEEKING BEHAVIOUR OF PNEUMONIA CHILDREN UNDER FIVE IN LUBUK BEGALUNG HEALTH CENTER 2024 : PNEUMONIA CHILDREN UNDER FIVE - Silvia Amanda Lodi; Ade Suzana Eka Putri; Yeffi Masnarivan (STIKes Mandala Waluya Kendari, 2026)
Background: The Lubuk Begalung Community Health Centre has the highest number of pneumonia cases among children under five from 2020 to 2023. Pneumonia is a leading cause of infection-related mortality in children under five. Poor health seeking behaviour may lead to complications and increase the risk of death. This study aimed to determine the factors associated with treatment-seeking behaviour for pneumonia among children under five at the Lubuk Begalung Community Health Centre. Methods: This study uses an analytical research type with a cross-sectional design and was conducted from February to June 2024 at the Lubuk Begalung Community Health Centre. The sample in this study consisted of 87 respondents. Data were analysed using univariate, bivariate, and multivariate analyses. Results: The statistical test results showed that 62.1% of respondents had poor health-seeking behaviour for pneumonia among children under five. Bivariate analysis indicated that mother’s age (p = 0.004; PR = 1.719; 95% CI: 1.190–2.483), mother’s knowledge (p < 0.0001; PR = 3.063; 95% CI: 2.049–4.578), and perceived disease severity (p = 0.014; PR = 1.587; 95% CI: 1.109–2.270) were associated with health-seeking behaviour for pneumonia among children under five. Binary logistic regression analysis showed that family income was associated with health-seeking behaviour (p = 0.017; PR = 16.406; 95% CI: 1.642–163.900). Conclusion: Health-seeking behavior for pneumonia among children under five is influenced by maternal age, maternal knowledge, and the perceived severity of the illness, with family income being the most dominant factor. Therefore, enhanced health education efforts are needed by the Padang City Health Office and the Lubuk Begalung Community Health Center, particularly regarding the symptoms and danger signs of pneumonia, as well as the importance of seeking early treatment at healthcare facilities.